Release and distribution of Lilioceris cheni (Coleoptera: Chrysomelidae), a biological control agent of air potato (Dioscorea bulbifera: Dioscoreaceae), in Florida. Issue 8 (2nd August 2016) - Overholt, William A.; Rayamajhi, Min; Rohrig, Eric; Hight, Stephen; Dray, F. Allen; Lake, Ellen; Smith, Melissa; Hibbard, Ken; Bhattarai, Ganesh P.; Bowers, Kristen; Poffenberger, Ryan; Clark, Molly; et al.
ABSTRACT: From 2012 to 2015, 429, 668 Lilioceris cheni Gressit and Kimoto (Coleoptera: Chrysomelidae) were released in Florida for biological control of air potato Dioscorea bulbifera L. (Dioscoreaceae). In the fall of 2015, a state-wide survey was conducted at 113 randomly selected air potato infestations in order to determine the spatial distribution of L. cheni . Damage due to L. cheni was found at 86% of locations and was low in the Florida panhandle where air potato was relatively uncommon and fewer beetles had been released, and in far south Florida, despite high numbers of beetle releases. On average, beetles travelled 9.5 km from the nearest release site to survey sites from the date of release to the time of the survey, with a maximum distance of nearly 67 km. The rate of spread was estimated at 8.2 km/year under the assumption that beetles present at survey sites migrated or were moved from the nearest release site. Air potato vines produced fewer aerial tubers, the vegetative propagule of air potato, as foliar damage due to L. cheni increased. The results suggest that future research efforts should focus on determining the biotic and abiotic factors that may be limiting establishment in some areas of Florida.